1988
DOI: 10.1139/g88-056
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic stability of maize tissue cultures: a cell line pedigree analysis

Abstract: Cytogenetic instability in maize plants regenerated from tissue culture is a commonly observed phenomenon. In an attempt to understand the origin of this instability meiotic analyses were performed on 370 regenerated plants that were initiated from cell lines of 22 immature embryos of 9 maize genotypes. Cell lineage pedigrees were maintained on these cultures to record the familial relationship between regenerated plants. Overall, 12.4% of the 370 régénérants contained cytological aberrations. The largest cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
5

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 1 publication
0
15
0
5
Order By: Relevance
“…These facts suggest that the conditions which are favourable for polyploidization of the calli probably are unfavourable for the morphogenesis of higher levels of polyploids. It may be concluded that in cultured tissues, there is a progressive accumulation of irregularities of chromosomes which increases with the aging process during long term sub-culturing and that these tissues have a reduced potentiality for morphogenesis (Benzion and Phillips (1988).…”
Section: Resultsmentioning
confidence: 99%
“…These facts suggest that the conditions which are favourable for polyploidization of the calli probably are unfavourable for the morphogenesis of higher levels of polyploids. It may be concluded that in cultured tissues, there is a progressive accumulation of irregularities of chromosomes which increases with the aging process during long term sub-culturing and that these tissues have a reduced potentiality for morphogenesis (Benzion and Phillips (1988).…”
Section: Resultsmentioning
confidence: 99%
“…In culture, when cells arc induced into rapid cell division, the presence of heterochromatin may therefore lead to enhanced levels of breakage in those chromosomes which contain it. Correlations between the location of tissue culture-induced chromosome breakage and the distribution of heterochromatin have been demonstrated in many species (2,12,18). However, chromosome breakage still occurs in plants wit11 little heterochromatin (I) suggesting tl1at other aspects of genome composition must also be i.mport:mt.…”
Section: Mechanisms Associated With Errors In Cell Division In Vitromentioning
confidence: 99%
“…In oats, plants regenerated from 20-month-old cultures of the Tippecanoe and Lodi varieties carried a detectable structurally-altered chromosome 49% and 88% of the time, respectively (41). In maize, 1036 regenerated plants were analyzed meiotically (2,42,43,44). Of these, 217 (21%) possessed detectable structurally-altered chromosomes.…”
Section: Late Replication-induced Chromosome Breakagementioning
confidence: 99%